Theories of Niche Construction and Optimal Foraging: weaknesses and virtues in understanding the early stages of domestication - Lins Neto, Ernani Machado de Freitas; Albuquerque, Ulysses (Ethnobiology and Conservation, 2018)
The transition from hunter-gatherer condition to the development of agricultural practices has provided one of the greatest technological advances of humanity. In view of the importance of this phenomenon and still persistent gaps, theoretical models emerge to elucidate issues related to the beginning of the domestication of animals and plants, a crucial moment for understanding socioecological and evolutionary factors that are determinant for environmental manipulation. Two theoretical models are relevant in this discussion: theories of optimal foraging and niche construction. In this sense, this mini-review highlights the debate of these two perspectives on the beginning of domestication highlighting weaknesses and virtues of each proposal.